EFL Program Management in Turkish Cypriot Educational Context: Qualitative Case Study - Chinaza Solomon Ironsi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
This study is carried out to examine EFL program managers’ working conditions, eliciting information on their views on EFL program management within the Turkish Cypriot context. This study also upholds that an understanding of their perceptions as EFL program managers will help create a better working condition and improve EFL programs and instruction, characterized by excessive proliferation of language centers that put profit-making as their utmost priority. Two research questions were utilized to investigate EFL program managers’ challenges and barriers while managing foreign language institutes and centers. The study adopted a qualitative research design approach; 45 EFL program managers and coordinators with international qualifications with over ten years of experience were purposefully sampled and recruited as participants for this study. A semi-structured interview was the instrument for data collection, which experts validated to ensure it measures what it purports to measure. Data collected were transcribed and analyzed through thematic analysis to uncover themes used to define and interpret findings. This study’s findings indicate that the absence of professional expertise, training/retraining programs, resource availability, and competition from other universities were the significant challenges EFL program managers face while carrying out their duties. It was also unveiled that over monetization of EFL programs within institutions brings about challenges in program management. Recommendations were given to bridge these gaps.